Strategic Cognition and Issue Salience: Toward an Explanation of Firm Responsiveness to Stakeholder Concerns - Bundy, Jonathan; Shropshire, Christine; Buchholtz, Ann K. (Academy of Management Review, 2013)
As a new perspective for understanding firm responsiveness to stakeholder concerns, we propose a strategic cognition view of issue salience—that is, the degree to which a stakeholder issue resonates with and is prioritized by management. Specifically, we explain how a firm's cognitive structures of organizational identity and strategic frames use different core logics to influence managerial interpretation of an issue as salient. We then present a typology of firm responsiveness and suggest that firms will respond more substantially to those issues perceived as salient to both cognitive logics and more symbolically to those issues perceived as salient to only one logic. This article fills key gaps in our understanding of how firms manage and respond to stakeholders by focusing on the salience of the issue and incorporating strategic cognition as a key mediating mechanism.